Phloxine B as a probe for entrapment in microcrystalline cellulose - Duarte, P. (2012)
The photophysical behaviour of phloxine B adsorbed onto microcrystalline cellulose was evaluated by reflectance spectroscopy and laser induced time-resolved luminescence in the picosecond-nanosecond and microsecond- millisecond ranges. Analysis of the absorption spectral changes with concentration points to a small tendency of the dye to aggregate in the range of concentrations under study. Prompt fluorescence, phosphorescence and delayed fluorescence spectral decays were measured at room temperature and 77 K, without the need of sample degassing because cellulose protects triplet states from oxygen quenching. In all cases, spectral changes with time and lifetime distribution analysis were consistent with the dye coexisting in two different environments: dyes tightly entrapped between polymer chains in crystalline regions of cellulose showed longer fluorescence and phosphorescence lifetimes and more energetic triplet states, while dyes adsorbed in more amorphous regions of the support showed shorter lifetimes and less energetic triplet states. This behaviour is discussed in terms of the different dye-support interactions in both kinds of adsorption sites.